Effect of organic silicon quaternary ammonium salts on mitigating corrosion of reinforced steel induced by SRB in mild alkaline simulated concrete pore solution. (20th February 2021) - Etim, Ini-Ibehe Nabuk; Dong, Junhua; Wei, Jie; Nan, Chen; Pokharel, Durga Bhakta; Umoh, Aniefiok Joseph; Xu, Dake; Su, Mingzhong; Ke, Wei
Abstract: The corrosion damage of 20SiMn steel by sulphate-reducing bacteria (SRB) and the mitigation effect of organic silicon quaternary ammonium salt (OSA) were studied in sterilized mild alkaline simulated concrete pore solution (STR) with different additions of SRB and OSA at pH 9.35 for 28 days. Uniform corrosion occurs in STR medium while slight localized corrosion is observed in STR + OSA medium, and localized pitting corrosion occurs in STR + SRB and STR + SRB + OSA media. The largest pit depth reduces from 36.70 μm in STR + SRB medium to 3.31 μm in STR + SRB + OSA medium due to the mitigation effect of OSA. The corrosion rate reflected by weight loss and electrochemical impedance spectroscopy (EIS) results presents the order of STR < STR + OSA < STR + SRB + OSA < STR + SRB, which also proves that the presence of SRB can accelerate corrosion in a carbonated medium. However, OSA as an efficient bacteriostatic agent can reduce the excessive growth of SRB and thus reduce corrosion.